Major components of energy drinks (caffeine, taurine, and guarana) exert cytotoxic effects on human neuronal SH-SY5Y cells by decreasing reactive oxygen species production - Zeidán-Chuliá, Fares; Gelain, Daniel Pens; Kolling, Eduardo Antônio; Rybarczyk-Filho, José Luiz [UNESP]; Ambrosi, Priscilla; Resende Terra, Silvia; Pires, André Simões; Da Rocha, João Batista Teixeira; Antônio Behr, Guilherme; Fonseca Moreira, José Cláudio (Hindawi, 2013)
Scope. To elucidate the morphological and biochemical in vitro effects exerted by caffeine, taurine, and guarana, alone or in combination, since they are major components in energy drinks (EDs). Methods and Results. On human neuronal SH-SY5Y cells, caffeine (0.125-2 mg/mL), taurine (1-16 mg/mL), and guarana (3.125-50 mg/mL) showed concentration-dependent nonenzymatic antioxidant potential, decreased the basal levels of free radical generation, and reduced both superoxide dismutase (SOD) and catalase (CAT) activities, especially when combined together. However, guarana-treated cells developed signs of neurite degeneration in the form of swellings at various segments in a beaded or pearl chain-like appearance and fragmentation of such neurites at concentrations ranging from 12.5 to 50 mg/mL. Swellings, but not neuritic fragmentation, were detected when cells were treated with 0.5 mg/mL (or higher doses) of caffeine, concentrations that are present in EDs. Cells treated with guarana also showed qualitative signs of apoptosis, including membrane blebbing, cell shrinkage, and cleaved caspase-3 positivity. Flow cytometric analysis confirmed that cells treated with 12.5-50 mg/mL of guarana and its combinations with caffeine and/or taurine underwent apoptosis. Conclusion. Excessive removal of intracellular reactive oxygen species, to nonphysiological levels (or antioxidative stress), could be a cause of in vitro toxicity induced by these drugs. © 2013 Fares Zeidán-Chuliá et al.
Keywords: Anti-oxidative stress; Concentration-dependent; Flow-cytometric analysis; Free radical generation; Membrane blebbing; Non-enzymatic antioxidants; Reactive oxygen species; Superoxide dismutases; Amino acids; Beverages; Cell death; Cytotoxicity; Emergency rooms; Free radicals; Neurons; Oxygen; Caffeine; caffeine; caspase 3; catalase; guarana extract; reactive oxygen metabolite; superoxide dismutase; taurine; apoptosis; controlled study; cytotoxicity; energy drink; enzyme activity; human; human cell; in vitro study; nerve cell degeneration; neurite; protein cleavage